Special AT‐rich sequence‐binding protein 2 (Satb2) synergizes with Bmp9 and is essential for osteo/odontogenic differentiation of mouse incisor mesenchymal stem cells. (4th March 2021) - Chen, Qiuman; Zheng, Liwen; Zhang, Yuxin; Huang, Xia; Wang, Feilong; Li, Shuang; Yang, Zhuohui; Liang, Fang; Hu, Jing; Jiang, Yucan; Li, Yeming; Zhou, Pengfei; et al.
Abstract: Objectives: Mouse incisor mesenchymal stem cells (MSCs) have self‐renewal ability and osteo/odontogenic differentiation potential. However, the mechanism controlling the continuous self‐renewal and osteo/odontogenic differentiation of mouse incisor MSCs remains unclear. Special AT‐rich sequence‐binding protein 2 (SATB2) positively regulates craniofacial patterning, bone development and regeneration, whereas SATB2 deletion or mutation leads to craniomaxillofacial dysplasia and delayed tooth and root development, similar to bone morphogenetic protein (BMP) loss‐of‐function phenotypes. However, the detailed mechanism underlying the SATB2 role in odontogenic MSCs is poorly understood. The aim of this study was to investigate whether SATB2 can regulate self‐renewal and osteo/odontogenic differentiation of odontogenic MSCs. Materials and methods: Satb2 expression was detected in the rapidly renewing mouse incisor mesenchyme by immunofluorescence staining, quantitative RT‐PCR and Western blot analysis. Ad‐ Satb2 and Ad‐si Satb2 were constructed to evaluate the effect of Satb2 on odontogenic MSCs self‐renewal and osteo/odontogenic differentiation properties and the potential role of Satb2 with the osteogenic factor bone morphogenetic protein 9 ( Bmp 9 ) in vitro and in vivo. Results: Satb2 was found to be expressed in mesenchymal cells and pre‐odontoblasts/odontoblasts. We further discovered that Satb2 effectively enhances mouse incisor MSCs self‐renewal. Satb2 acted synergistically with the potent osteogenic factor Bmp9 in inducing osteo/odontogenic differentiation of mouse incisor MSCs in vitro and in vivo. Conclusions: Satb2 promotes self‐renewal and osteo/odontogenic differentiation of mouse incisor MSCs. Thus, Satb2 can cooperate with Bmp9 as a new efficacious bio‐factor for osteogenic regeneration and tooth engineering. Abstract : The graphical abstract showed that Satb2 and Bmp9 were expressed in mesenchymal stem cells of mouse incisor growth region. Satb2 acted synergistically with the potent osteo/odontogenic factor Bmp9 in mouse incisor MSCs. Satb2 could as a new efficacious bio‐factor for osteogenic regeneration and tooth engineering in cooperation with Bmp9 .